PERAN LEMBAGA KEUANGAN NON BANK TERHADAP MASYARAKAT - Riky Soleman; Basaria Nainggolan (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2022)
The Department of Industry and Trade is a community empowerment institution. Empowerment has been carried out in various forms and variations, it has the aim of directing people's lives towards a better direction, because the main goal of empowerment is the achievement of community welfare, besides that the task of the agency is as an organizer. This public service is intended to provide services to the community based on community needs. This research is a descriptive qualitative field research with primary data collection through in-depth interviews with employees of the Department of Industry and Trade of the Yogyakarta Special Region Government study, while secondary data is obtained from various literatures such as books and journals. The results of this study are the presence of the Department of Industry and Trade to provide benefits by providing guidance to the community, conducting training with these business actors from the production and marketing aspects in terms of providing facilitation to increase the use of technology for business actors to help provide equipment provided to them with the intention of being able to increase the volume of their production, then increase from the market aspect the agency provides for the public to participate such as exhibition events both locally, nationally and internationally, the agency also organizes exhibitions to include them so that their ability to market products is further increased. We do this to increase the community's production business.Keywords: Role, Department of Industry and Trade, Society